Economic and Legal Regulation of Educational Processes in the Field of Natural Sciences and Humanities - TONKIKH, Aleksandr P.; DANILOVA, Tatyana V.; PRYADEKHO, Aleksey A. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018DO - 10.14505//jarle.v9.7(37).33, 2019)
Among the most important issues that need to be addressed in order to improve higher professional education is the issue of proper and complete regulation of relations in the educational system of the Russian Federation at the legislative level. Only by ensuring proper legal regulation of higher professional education is it possible to achieve the main goal defined by the Constitution of the Russian Federation, namely, to ensure and protect the right of a citizen of the Russian Federation to receive a decent and desirable education. Legal regulation of higher professional provides a purposeful activity to streamline the existing and emerging social relations in the context of modernization of the HPE. Analysis of the state of legal regulation involves the analysis of sources regulating the legal relationship. As in other spheres of public life, the system of higher education has both international legal and national legal sources. This is explained by the fact that the system of law includes large interacting blocks ‒ a block of domestic (national) law and a block of those universally recognized principles and norms of international law that are included in the relevant system of law.